Il De errore profanarum religionum DI Firmico Materno nel Carm. 19 DI Paolino DI Nola - Guttilla, Giuseppe (Revue d'études augustiniennes et patristiques, 2006)
Who reads Paulinus’ Poem 19, 95-195 is certainly impressed by something new that he finds there, concerning not only its doctrinal and argumentative content, but also its form, that sometimes appears too polemical or realistic. Even if up to now nobody has referred Paulinus’ ratio poetandi to some author that for some reason remains unknown to us, he really exists and we can mention his name. It is Firmicus Maternus, whose work De errore profanarum religionum was composed around 346 A. D. After 350 this work is not quoted by Christian authors any more and the Fathers who fight against paganism in between the end of the fourth century and the beginning of the fifth are not interested in it. On the contrary Paulinus knows well enough this work and initially he uses it in his epist. 31, 3 and later on, in a more extensive way, in his Poem 19.